2002
DOI: 10.1086/338004
|View full text |Cite
|
Sign up to set email alerts
|

The Shikimate Pathway and Its Branches in Apicomplexan Parasites

Abstract: The shikimate pathway is essential for production of a plethora of aromatic compounds in plants, bacteria, and fungi. Seven enzymes of the shikimate pathway catalyze sequential conversion of erythrose 4-phosphate and phosphoenol pyruvate to chorismate. Chorismate is then used as a substrate for other pathways that culminate in production of folates, ubiquinone, napthoquinones, and the aromatic amino acids tryptophan, phenylalanine, and tyrosine. The shikimate pathway is absent from animals and present in the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
83
1
3

Year Published

2005
2005
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 136 publications
(90 citation statements)
references
References 95 publications
2
83
1
3
Order By: Relevance
“…Based on these results, Roberts C. W. et al 48) suggested that glyphosate or other inhibitors of the shikimate pathway might be good antimalarials. Considering the high IC 50 of glyphosate, this compound has not been further studied or developed for treatment for malaria.…”
Section: Discussionmentioning
confidence: 99%
“…Based on these results, Roberts C. W. et al 48) suggested that glyphosate or other inhibitors of the shikimate pathway might be good antimalarials. Considering the high IC 50 of glyphosate, this compound has not been further studied or developed for treatment for malaria.…”
Section: Discussionmentioning
confidence: 99%
“…The importance of the shikimate pathway is exemplified by the common herbicide glyphosate, which inhibits the enzyme 5-enolpyruvylshikimate-3-phosphate synthase. Recent studies have also shown that glyphosate blocks the shikimate pathway in apicomplexan parasites and is effective in controlling their growth (3). The shikimate pathway consists of seven enzymatic steps initiated by the condensation of phosphoenolpyruvate and erythrose-4-phosphate by 3-deoxy-Darabino-heptolosonate 7-phosphate synthase.…”
mentioning
confidence: 99%
“…The only other enzyme known to catalyze a similar reaction is 5-enolpyruvyl shikimate-3-phosphate synthase (EC 2.5.1.19), also known as EPSPS or AroA. 5-Enolpyruvyl shikimate-3-phosphate synthase is the sixth enzyme in the shikimate pathway toward the synthesis of aromatic amino acids in microorganisms and plants (7,8). Both enzymes exist in an open, substrate-free state and a closed, liganded state, indicating that their reactions follow an induced-fit mechanism (9 -13).…”
mentioning
confidence: 99%